TECTONIC RIFTING OF UPPER PALEOZOIC – MESOZOIC INTRA-CRATONIC BASINS IN THE SOUTHEASTERN GONDWANALAND AND ITS ECONOMIC ASPECTS: with refference to the Geology of North Sumatra and West Australia - Amiruddin, Amiruddin (Pusat Survei Geologi, 2011)
Lower Permian fluvio – marine glacial sediments of intracratonic basins of West Australia and these of North Sumatera, West Indonesia in addition paleomagnetic data indicate that the paleo position of all basins were probably in the Southeastern part of Gondwanaland. These are also evidence that during Permian, glaciation had been widespread occur in the part of the land. The occurence of ultrapotassic rocks comprising Permian – Triassic A-type granite (An orogenic-type granite) in north Sumatera terrain and feldspatoid bearing subvolcanics of the Canning Basin, West Australia suggests that a tectonic rifting happened during the time period in the part of that stable continental plate and give way for magmatic emplacemet from lower to upper crusts. Perhaps this rifting had also related to a convergent activity during that time in which proto Pacific Plate move westward and collided or subducted into the eastern part of proto Australia continent moving eastwards and eventually form a Permian-Triassic mobile belt along Eastern Australia known as Tasman mobile belt.Key word: tectonic rifting, intra-cratonic basin, Gondwanaland, Permian – Triassic, North Sumatra, West Australia.